Ischemic heart disease probability in athletes: detection and forecast rate - Dalskiy, D. D.; Kraev, S. A.; Afanasieva, I. A.; Naumenko, E. V. (Theory and Practice of Physical Culture, 2017)
As demonstrated by a few recent studies by European and American sport medicine specialists, most of the sudden deaths of athletes could be prevented if the fatal cardiac diseases or overtraining conditions were diagnosed in a timely manner. The relevant national governments have made decisions to perform obligatory health screenings of beginner athletes (aged 12-14 years which is the traditional beginner age for most of the sport disciplines) (M.V. Chashin, R.V. Konstantinov, 2010).